International transformation and regime survival in North Korea: Marketization and nuclear program - López Aymes, Juan Felipe (2023)
Despite world transformations in the last 30 years, and the economic and humanitarian crisis in North Korea, the political regime has prevailed and is not seemingly about to end. This article discusses two underlying factors that provide stability for survival: on the one hand, it maintains a centrally planned economy, but under an informal arrangement that tolerates black markets and some levels of corruption; on the other hand, the nuclear program contributes to maintain certain domestic cohesion between the Workers Party and the military sector, but also legitimates the regime’s continuity against real or fabricated external threats. It concludes that power foundations of Pyongyang’s rule remain in place, so it’s still possible that it will overcome present and future adversities, that Kim’s family keep some internal and external political leverage, and may remain in power indefinitely.